WACANA ANTI MADZHAB MUATAN MATERI FIKIH DALAM BUKU AJAR PENDIDIKAN AGAMA ISLAM - Muqoffi, Muqoffi; Sutiah, Sutiah; Marno, Marno; Fahmi, Fahmi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This study examines the phenomenon of anti-madzhab discourse in the fiqh materials of Islamic education textbooks widely circulated in Indonesian schools and madrasahs. By employing a qualitative library study approach, this research analyzes primary references for mazhab comparison, including Al-Fiqhu ‘alā Al-Madzāhib Al-Arba’ah by Abdu al-Rahman al-Jaziri and Al-Mausū’ah Al-Fiqhiyah Al-Kuwaitiyyah by some Kuwait scholars. The findings reveal that several fiqh-related topics in the textbooks, such as the conditions for valid ablution, requirements to become an imam, timing for zakat payment and identification of zakat recipients, reflect some anti-madzhab perspectives. These perspectives can lead to al-masyaqqah (difficulties) in worship practices within the community. The study highlights the need for a thorough evaluation of Islamic education textbooks, recommending that fiqh materials incorporate traditional madzhab frameworks to enhance their alignment with Islamic religious education standards. This research contributes to the ongoing discourse on curriculum development and the importance of maintaining doctrinal integrity in educational resources.